Plasma citrulline correlates with basolateral amino acid transporter LAT4 expression in human small intestine. Issue 4 (April 2021) - Maric, Stefano; Flüchter, Pascal; Guglielmetti, Laura Chiara; Staerkle, Ralph Fabian; Sasse, Tom; Restin, Tanja; Schneider, Christoph; Holland-Cunz, Stefan Gerhard; Crenn, Pascal; Vuille-dit-Bille, Raphael Nicolas
Summary: Background & aims: Plasma citrulline, a non-protein amino acid, is a biochemical marker of small intestine enterocyte mass in humans. Indeed, citrulline is highly correlated with residual bowel length in patients with short bowel syndrome. It is known to be synthesised in epithelial cells of the small intestine from other amino acids (precursors). Citrulline is then released into systemic circulation and interconverted into arginine in kidneys. If plasma citrulline concentration depends on abundance of intestinal amino acid transporters is not known. The aim of the present study was to explore whether plasma citrulline concentration correlates with the expression of intestinal amino acid transporters. Furthermore, we assessed if arginine in urine correlates with plasma citrulline. Methods: Duodenal samples, blood plasma and urine were collected from 43 subjects undergoing routine gastroduodenoscopy. mRNA expression of seven basolateral membrane amino acid transporters/transporter subunits were assessed by real-time PCR. Plasma and urine amino acid concentrations of citrulline, its precursors and other amino acids were analysed using High Performance Liquid Chromatography measurements. Amino acid transporter mRNA expression was correlated with blood plasma and urine levels of citrulline and its precursors using Spearman's rank correlation. Likewise, urine arginine was correlated with plasma citrulline. Results: Plasma citrulline correlated with the mRNA expression of basolateral amino acid transporter LAT4 (Spearman's r = 0.467, p = 0.028) in small intestine. None of the other basolateral membrane transporters/transporter subunits assessed correlated with plasma citrulline. Plasma citrulline correlated with urinary arginine, (Spearman's r = 0.419, p = 0.017), but not with urinary citrulline or other proteinogenic amino acids in the urine. Conclusions: In this study, we showed for the first time that small intestinal basolateral LAT4 expression correlates with plasma citrulline concentration. This finding indicates that LAT4 has an important function in mediating citrulline efflux from enterocytes. Furthermore, urine arginine correlated with plasma citrulline, indicating arginine in the urine as possible additional marker for small intestine enterocyte mass. Finally, basolateral LAT4 expression along the human small intestine was shown for the first time.